Force spectroscopy determination of Young's modulus in mixed matrix membranes. (7th November 2018) - Longo, Mariagiulia; De Santo, Maria Penelope; Esposito, Elisa; Fuoco, Alessio; Monteleone, Marcello; Giorno, Lidietta; Jansen, Johannes Carolus
Abstract: This paper presents Atomic Force Microscopy (AFM) as a powerful alternative to the more commonly used tensile tests for the analysis of the mechanical properties of polymeric membranes. The Young's modulus measurements by the traditional tensile tests were compared with AFM operated in Force Spectroscopy mode. AFM measurements were carried out with nanometric and micrometric tips on dense membranes of neat Pebax ® 1657 and on mixed matrix membranes of Pebax ® 1657 with different concentrations of the ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate, [BMIM][BF4 ]. The use of a nanometric AFM tip enables the determination of the local Young's modulus of the individual domains of the microphase-separated block-copolymer, while a larger tip gives average values of the bulk polymer. We found excellent correlation between the data obtained with common tensile tests and those obtained in compression by AFM with the micrometric tip, with important additional information on morphological features, when using the nanometric tip. This offers good perspectives for the analysis of samples where traditional tensile tests cannot be used, for instance composite membranes or particularly small samples. Graphical abstract: Highlights: Self-standing [BMIM][BF4 ]/Pebax ® 1657 membranes were successfully prepared. AFM force spectroscopy determines mechanical properties of membranes. Good quantitative agreement between tensile tests and force spectroscopy. Nano-scale and bulk properties can be analysed, depending on the tip size. A silicon environment reduces capillary forces and improves data quality.